Critical Appraisal of a Systematic Review: From Selection to Quality Assessment of Primary Studies - Azevedo, Luís Filipe; Sousa-Pinto, Bernardo (Journal of the Portuguese Society of Anesthesiology, 2019)
The first steps required for performing a systematic review include the definition of the research question and the search for primary studies. The latter typically results in a large quantity of potentially relevant studies, but only a minority of them end up being included in the systematic review. This prompts the need for a selection process that aims to identify the primary studies complying with the eligibility criteria. The selection of primary studies must be independently performed by at least two researchers. This process comprises two phases – the screening phase (where studies are selected based on title and abstract reading) and the inclusion phase (requiring full text reading). After completing the selection process, researchers should extract relevant data and information and assess the quality of primary studies included. Quality assessment should be performed based on predefined tools and criteria. Such assessment is important not only to evaluate the quality of the existing evidence regarding a particular research question, but also to identify methodological practices that future studies should take into account, or to help in the process of qualitative and quantitative evidence synthesis.